Estimated Glomerular Filtration Rate Is Associated With an Increased Risk of Death in Heart Failure Patients With Preserved Ejection Fraction - Chen, Zhuo; Lin, Qian; Li, Jingen; Wang, Xinyi; Ju, Jianqing; Xu, Hao; Shi, Dazhuo (Frontiers in Cardiovascular Medicine, 2021)
Background: Renal dysfunction is associated with adverse cardiovascular outcomes in patients with heart failure (HF), but its impact on patients with heart failure with preserved ejection fraction (HFpEF) remains unclear. Methods: 3,392 subjects of the TOPCAT (Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist) trial were assigned to two groups by estimated glomerular filtration rate (eGFR) ≥ 60 ml/min/1.73 m2 or 30–59 ml/min/1.73 m2. The outcomes, including all-cause death, cardiovascular death and HF hospitalization, were examined by multivariable cox models. Results: Over a median follow-up of 3.4 ± 1.7 years, a total of 524 all-cause deaths, 334 cardiovascular deaths and 440 HF hospitalizations occurred. Compared with patients with eGFR ≥ 60 ml/min/1.73 m2, those with eGFR 30–59 ml/min/1.73 m2 were associated with an increased risk of the all-cause death [adjusted hazard ratio (HR), 1.47; 95% confidence interval (CI), 1.24–1.76; P < 0.001], cardiovascular death (adjusted HR, 1.53; 95% CI: 1.23–1.91; p < 0.001), and HF hospitalization (adjusted HR: 1.21; 95% CI: 1.00–1.47; p = 0.049) after multivariable adjustment for potential confounders. Conclusions: eGFR 30–59 ml/min/1.73 m2 was related to an increased risk of all-cause death, cardiovascular death and HF hospitalization in HFpEF patients.